Development and analysis of nitrogen-doped amorphous InGaZnO thin film transistors. (15th June 2017) - Xie, Haiting; Xu, Jianeng; Liu, Guochao; Zhang, Lei; Dong, Chengyuan
Abstract: The nitrogen-doped (N-doped) amorphous InGaZnO thin film transistors ( a -IGZO TFTs) were investigated against the undoped and oxygen doped (O-doped) devices. The N-doped a-IGZO TFTs exhibited better electrical performance and bias stress stability, and especially more stable thermal properties. The X-ray photoemission spectroscopy (XPS) measurements were carried out at different temperatures (298 K and 393 K) to examine the physical essence of the thermal instability of undoped, O-doped, and N-doped a-IGZO TFTs. The XPS characterization results indicated that nitrogen doping caused lesser oxygen vacancy variation with the temperature (0.6%) compared with undoping (7.2%) and oxygen doping (11.8%). Hence, the a-IGZO TFTs with N-doped active layers had much better stability than those with undoped and O-doped active layers.